Profil dan Potensi Antikanker Ekstrak Etanol 96% Temu Giring (Curcuma heyneana) Pada Sel MCF-7 - Misgiati, Misgiati; Andini, Andini; In Oktavia, Anggraeni; Rosyidah, A’liyatur (Jurusan Farmasi Universitas Negeri Gorontalo, 2024)
The use of natural ingredients for cancer treatment is something that needs to be considered to obtain treatment according to the right molecular target cells with high selectivity with minimal side effects. Temu giring (Curcuma heyneana) has the highest antioxidant activity among the rhizome groups; the content of secondary metabolites is polyphenols and flavonoids. There was a correlation between antioxidant activity and cancer activity. The aim of this study was to examine the profile and anticancer activity of MCF-7 cells treated with a 96% ethanol extract of temu giring. Extraction using the maceration method. The profile of temu giring extract uses chemical reactions and thin layer chromatography. Anticancer testing using the Microculture Tetrazolium Technique assay method. Testing using MCF-7 cells with extract concentrations of 400µL, 200µL, 100µL, 50µL, and 25µL. Extract yield: 5.17%. Secondary metabolites in turmeric extract are flavonoids, terpenoids, polyphenols, and anthraquinones. The metabolites have the ability to inhibit MCF-7 cells. The anticancer potential of MCF-7 cells with IC50 60.38±9.03µL (strong cytotoxicity).